Understanding terrorism challenges, perspectives, and issues - Martin, Gus (SAGE, 2013)
The Fourth Edition of Gus Martin's Understanding Terrorism, once again offers a multidisciplinary, comprehensive exploration of contemporary terrorism that helps readers develop the knowledge and skills they need to critically assess terrorism in general and terrorist incidents in particular. The Fourth Edition presents new, updated theories, cases, and incidents as well as new photographs, updated tables, and enhanced graphics. An entirely new chapter is devoted to homeland security in the United States and Europe.